المدّ الشيعي في البلدان الإسلامية: دراسة في الغايات والأساليب والآثار: The Purposes, Methods and Impacts of Shiite Doctrines’ Expansion in Islamic Countries - Abdo Amer, Abdulwahab Mahyoub Murshed; Abdo Amer, Eftekhar Ali (Afkar: Jurnal Akidah dan Pemikiran Islam, 2020)
The study discusses the Shiite doctrinal movement in terms of history, statehood, religion and sect. It will explain the influence of the movement in Islamic countries as well as the efforts made to spread the doctrine based on the authority of religious leaders and try to re-map the influence of the Shiite sect in Islamic countries. Researchers use descriptive analysis methodology to explain the doctrinal expansion. The study found that this movement used media and money to divide political stability of the Islamic countries. The theory of the Iranian Revolution, Umm al-QurÄ and Imam al-Mahdi were also used to spread Shiite influence in Islamic countries.